Formação em serviço: análise de uma proposta de formação construída por e para educadores - Penteado, Maria Emiliana Lima (2013)
This study aims to understand the process of constituting a specific proposal for in-service training. The research involves a situation of teacher training began in 2010 and continued in 2011/2012. The training proposal was conceived, organized and carried out by and for educators of a particular Board of Education, the Municipal School of São Paulo, with the purpose of the training and self-training, culminating in a meeting called "I Educators Seminar" involving about 1400 teachers, among them managers, teachers and other school employees. To achieve our objective we chose to describe, analyze and explain the process of incorporation of the proposed in-service formation through the senses and meanings made by one of the teachers devised and also those contained in material produced by the group of educators participating in the proposal. The procedures used to obtain the data of the research were: 1. Analysis of the text produced by the collective group of educators to justify the organization and implementation of the proposed in-service formation, 2. Interview with one of the organizers and educators devised the proposed in-service formation. Was used for data analysis - "meaning core" - as proposed by Aguiar and Ozella (2006). The research is based on sociohistorical perspective and uses the theoretical assumptions of Vygotsky (2004) and his followers to achieve the genesis of the phenomenon. In the analyzes, the search for effective and increase the participation of teachers, reveals, among various aspects identified as determining feature.It appears that the proposed formation set up: with intent defined, theoretically grounded; concerned to consider the training needs of teachers, with the purpose of enhancing teacher practice to give visibility to the work that develop at school, engaged in creating space conducive to discussion and reflection of daily school and teaching practices, to achieve a moment of analysis and intervention of teaching practices confronted with educational theories and finally, in trying to suppress the gap between theory and practice to achieve praxis. It is observed that the proposed training tries enable some indications that the national and international literature (Fullan, 1982, 2009; Imbernon, 2009, 2010; Guskey, 1995; Souza, 2006; Longarezi, Alves, 2009) has demonstrated certain proximity: ongoing formation should occur continuously, consider the working conditions of teachers, and involve the collective management team throughout the training process, with the primary objective: to improve the conditions of teaching and learning